2016
DOI: 10.1590/s1806-92902016000100005
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerin levels in pearl millet-based diets for Nellore young bulls in feedlot

Abstract: -The objective of this study was to find the best level of inclusion of crude glycerin (0, 60, 120, and 240 g kg −1 of dry matter of diet) in substitution of pearl millet in a feedlot diet. Twenty-eight Nellore young bulls with mean age of 18 months and average weight of 357±23.56 kg were used. The animals were distributed in a completely randomized design with four treatments and seven replications. The intakes of dry matter, crude protein, neutral detergent fiber, and total digestible nutrients were similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…The temperature of the carcass decreased (P < 0.05) as the chilling period increased, reaching less than 5°C after 16 h, which is the maximum recommended value to ensure the microbiological quality of the meat (DAVE; GHALY, 2011). The crude glycerin levels of the diet, in turn, did not influence (P > 0.05) the temperatures of the carcasses, which is explained by similar fat cover degree and conformation of the carcasses (MOREIRA et al, 2016). According to Klont et al (1999), heavier carcasses with higher conformation show lesser decrease in temperature, and consequently lesser pH decline, which is associated with the larger specific surface of the carcasses.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The temperature of the carcass decreased (P < 0.05) as the chilling period increased, reaching less than 5°C after 16 h, which is the maximum recommended value to ensure the microbiological quality of the meat (DAVE; GHALY, 2011). The crude glycerin levels of the diet, in turn, did not influence (P > 0.05) the temperatures of the carcasses, which is explained by similar fat cover degree and conformation of the carcasses (MOREIRA et al, 2016). According to Klont et al (1999), heavier carcasses with higher conformation show lesser decrease in temperature, and consequently lesser pH decline, which is associated with the larger specific surface of the carcasses.…”
Section: Resultsmentioning
confidence: 87%
“…The cold carcass weights in animals fed diets containing 0, 60, 120, and 240 g of crude glycerin were 230.7, 236.9, 237.4, and 243.0 kg, respectively. Moreira et al (2016) published the productive performance results of experimental animals.…”
Section: Resultsmentioning
confidence: 99%
“…Crude glycerin has been evaluated in cattle diets, and the results have indicated that there is an improvement in the average daily gain (ADG) and feed conversion (Moreira et al, 2016;Barros et al, 2018). Furthermore, the results of crude glycerin use seem to depend on diet composition (Hales et al, 2013), level of inclusion of this byproduct (Benedeti et al, 2016), and animal category (Maciel et al, 2016a;Maciel et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The use of crude glycerin in animal feeding has been the target of many research studies (FRANÇOZO et al, 2013;GÓRKA et al, 2013;MOREIRA et al, 2016a). Researchers have examined the use of this by-product in cattle feeding with regard to animal performance and carcass and meat quality, but results have been contradictory (LAGE et al, 2010;FRANÇOZO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have examined the use of this by-product in cattle feeding with regard to animal performance and carcass and meat quality, but results have been contradictory (LAGE et al, 2010;FRANÇOZO et al, 2013). In general, animal performance is expected to increase with the incorporation of crude glycerin because it improves energy-use efficiency, as observed by Moreira et al (2016a). However, because the inclusion of crude glycerin in ruminant diets increases the rumen production of gluconeogenic precursors (CHANJULA et al, 2014), Pethick et al (2004) suggested that total carcass fat and meat marbling are expected to increase.…”
Section: Introductionmentioning
confidence: 99%